The Study of Language Transfer in EFL Students’ Translation Work - Fikri, Nurul (Jurnal Pendidikan Non formal, 2023)
Speakers of several native languages now use English as their common language. However, English learners struggle to understand the language, especially when it differs from their mother tongues. We can draw a connection between the aforementioned statement and how accurate language shift requires a solid understanding of English to understand translation. As a result, the study titled "The Study of Language Transfer in EFL Students' Translation Work" was considered. It is crucial to understand that language transfer is the main mechanism through which languages change from the source to the target language when we examine translation. A transfer is an effect brought about by the parallels and discrepancies between the target language and any other language that has already (and possibly inadequately) been learned, according to Odlin (1989: 27). During the process of learning a second language, language transfer is one of the strategies students use to communicate in that language, both consciously and unconsciously. This issue generally arises when learners are unsure about how to properly express themselves, and it may lead to grammatical errors because the two languages' rules do not coincide. Learners' utterances display various types and frequencies of language transfer (L2) depending on their first language (L1) and level of proficiency in the second language (L2). According to Wanderley & Demmans (2020), proficiency raises a learner's awareness of L2 rules and their application. A learner who is less skilled will employ a transfer more frequently.